2021
DOI: 10.1111/jan.15002
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of nursing students’ intention to receive COVID‐19 vaccination: A multi‐university study in Saudi Arabia

Abstract: Aims: This study examined the predictors of student nurses' intention to vaccinate against COVID-19. We measured the nursing students' risk perceptions, anxiety, fears and beliefs on COVID-19 vaccine; attitudes towards it and vaccine literacy (VL).Design: This study is a multi-university study utilizing the quantitative, cross-sectional and predictive approach.Methods: Using convenience sampling (n = 1170), we surveyed 10 Saudi universities from November 26, 2020, to December 31, 2020. Forward stepwise multino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…Other reasons for COVID-19 vaccine hesitancy include individuals' concerns about the adverse effects of COVID-19 vaccines, lack of trust in COVID-19 vaccines, planning to wait and see if the vaccines are safe, believing that COVID-19 is not a serious disease, believing that there is no need for the vaccines or being not sure about their effectiveness [66,67]. Therefore, it is important for governments to work on educating the population against these conspiracy theories, as such theories could jeopardize the strategies to mitigate the spread of COVID-19 and prevent timely and wide vaccination coverage of the populations [64,68,69]. As of 17 September 2021, it was estimated that approximately 50% of the general population in Saudi Arabia was fully vaccinated against COVID-19 [70].…”
Section: Introductionmentioning
confidence: 99%
“…Other reasons for COVID-19 vaccine hesitancy include individuals' concerns about the adverse effects of COVID-19 vaccines, lack of trust in COVID-19 vaccines, planning to wait and see if the vaccines are safe, believing that COVID-19 is not a serious disease, believing that there is no need for the vaccines or being not sure about their effectiveness [66,67]. Therefore, it is important for governments to work on educating the population against these conspiracy theories, as such theories could jeopardize the strategies to mitigate the spread of COVID-19 and prevent timely and wide vaccination coverage of the populations [64,68,69]. As of 17 September 2021, it was estimated that approximately 50% of the general population in Saudi Arabia was fully vaccinated against COVID-19 [70].…”
Section: Introductionmentioning
confidence: 99%
“…Nursing students are at risk of COVID‐19 due to direct exposure to patients during their hospital training (Al‐Rawajfah et al, 2021). Vaccinating nursing students is undoubtedly crucial to ensure the continuous education and it protects them amidst the pandemic (Alshehry et al, 2021). A survey among nursing students in seven European universities reported 43.8% of vaccine acceptability rate (Park et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, non-Saudi nurses have higher perceived mental-wellbeing scores than Saudi nurses. This finding is backed by recent research (7), which revealed that nationality was a significant predictor of nurses' psychological burden. In their study, Filipino and Indian nurses achieved lower mean scores for depression, anxiety, and stress than Saudi nurses.…”
Section: Discussionmentioning
confidence: 83%
“…By the end of 2021, over 50% of healthcare professionals (including nurses) worldwide were neither fully vaccinated nor had no plans to do so ( 6 ). For instance, vaccination hesitancy has been one of the determinants of under-vaccination in some nurses ( 7 ). According to Reses et al ( 3 ), the reason for the high hesitancy status of getting vaccinated can be attributed to people's political views and a lack of confidence and trust in vaccine manufacturers.…”
Section: Introductionmentioning
confidence: 99%